2021
DOI: 10.3897/zse.97.57968
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of parallel miniaturisation in Microhylinae (Anura, Microhylidae), with the description of a new genus of diminutive South East Asian frogs

Abstract: The genus Microhyla Tschudi, 1838 includes 52 species and is one of the most diverse genera of the family Microhylidae, being the most species-rich taxon of the Asian subfamily Microhylinae. The recent, rapid description of numerous new species of Microhyla with complex phylogenetic relationships has made the taxonomy of the group especially challenging. Several recent phylogenetic studies suggested paraphyly of Microhyla with respect to Glyphoglossus Günther, 1869, and revealed three major phylogenetic lineag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 110 publications
2
11
0
Order By: Relevance
“…Our matrilineal genealogy is consistent with those of Matsui et al (2011), Peloso et al (2016), Nguyen et al (2019), Garg et al (2019), and Gorin et al (2020Gorin et al ( , 2021. The BI and ML genealogy showed that the monophyly of Microhylinae was not supported and the relationships among microhylid subfamilies remained unresolved (Nguyen et al 2019) (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our matrilineal genealogy is consistent with those of Matsui et al (2011), Peloso et al (2016), Nguyen et al (2019), Garg et al (2019), and Gorin et al (2020Gorin et al ( , 2021. The BI and ML genealogy showed that the monophyly of Microhylinae was not supported and the relationships among microhylid subfamilies remained unresolved (Nguyen et al 2019) (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Our matrilineal genealogy was consistent with previous studies based on mt DNA (e.g., Matsui et al 2005Matsui et al , 2011Hasan et al 2012;Matsui et al 2013;Howlader et al 2015;Wijayathilaka et al 2016;Seshadri et al 2016;Yuan et al 2016;Khatiwada et al 2017;Nguyen et al 2019;Garg et al 2019;and Hoang et al 2020). As shown in previous molecular analyses (Matsui et al 2011;Peloso et al 2016), Asian Microhyla species were divided into two geographical subgroups: the Southeast Asian subgroup was recently named as Nanohyla by Gorin et al (2021), with eight known species: N. annamensis, N. annectens, N. hongiaoensis, N. marmorata, N. nanapollexa, N. perparva, N. petrigena, and N. pulchella; and Pan-Asian, including all other South, Southeast, and East Asian members (Fig.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 79%
See 2 more Smart Citations
“…The genus Microhyla Tschudi, 1838 is the most widely distributed group across Asia. Currently the genus is comprised of 52 recognised species (Li et al, 2019; Biju et al, 2019; Gorin et al,2021) of which 13 species are known to occur in India, only four from north east region, one from Andaman and others from Western Ghats and southern states of India. Occurrence of M. pulchra and M. butleri in India is doubtful (Garg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%